Piano sonata no. 8 in C minor, op. 13, ed. by Moscheles - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (Eduard Hallberger; Stuttgart; Germany, 2024)
Mid-nineteenth century edition of the Piano Sonata no. 8 in C minor, op. 13, edited by Ignaz Moscheles and published by Eduard Hallberger in Stuttgart as no. 8 of the series "L. v. Beethoven's sämmtliche Sonaten für Pianoforte" in "Hallberger's Pracht-Ausgabe der Classiker."